The significance of early-onset malignant arrhythmias in ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention and their relationship with biomarkers - Romanović, Radoslav; Džudović, Boris; Djenić, Nemanja; Jović, Zoran; Spasić, Marjan; Djurić, Obrad; Hladiš, Andjelko; Malović, Dragana; Obradović, Slobodan (Vojnosanitetski pregled, 2024)
Background/Aim. Patients who were treated with primary percutaneous coronary intervention (pPCI) and survived ventricular tachycardia (VT) and ventricular fibrillation (VF) in the first 48 hrs after ST-elevation myocardial infarction (STEMI) had, in most investigations, a similar long-term prognosis of the outcome, compared to those patients who did not have VT and VF during the first 48 hrs after STEMI. The aim of the study was to determine the association of myocardial infarction markers: creatine kinase-MB fraction (CK-MB), heart failure marker – B-type natriuretic peptide (BNP), and systemic inflammation factor – C-reactive protein (CRP) with early VT and VF onset, in relation to patient mortality during the first six months after STEMI. Methods. The retrospective study included 971 patients with STEMI treated with pPCI for ten years. VF and sustained VT (sVT) were detected outside of the hospital and during the first 48 hrs of hospitalization. Results. During the first 48 hrs from admission, 108 (11.1%) patients had life-threatening arrhythmias, of which 75 (69.4%) had VF, and 33 (30.6%) had sVT and were treated with direct current – DC shock and intravenous amiodarone. Intrahospital mortality was significantly higher in patients with VF/sVT in the first 48 hrs compared to patients without VF/sVT (14.8% vs. 5.7%, p = 0.001). BNP level had higher accuracy in the prediction of six-month death than the maximum blood level of CRP in patients without VF/sVT after 48 hrs. However, in patients with early-onset malignant arrhythmias, BNP showed a lower level of accuracy in predicting the six-month mortality, as did the CRP values, which had almost the same level of accuracy. Admission glycemia had a much lower predictive value in both groups of patients compared to BNP and CRP [0.705 (0.628–0.781), p
Keywords: biomarkers; mortality; percutaneous coronary intervention; prognosis; st elevation myocardial infarction; tachycardia, ventricular; ventricular fibrillation.